Assessing the safety and pharmacokinetics of the anti-HIV monoclonal antibody CAP256V2LS alone and in combination with VRC07-523LS and PGT121 in South African women: study protocol for the first-in-human CAPRISA 012B phase I clinical trial. Issue 11 (26th November 2020) - Mahomed, Sharana; Garrett, Nigel; Karim, Quarraisha A; Zuma, Nonhlanhla Y; Capparelli, Edmund; Baxter, Cheryl; Gengiah, Tanuja; Archary, Derseree; Samsunder, Natasha; Rose, Nicole D; Moore, Penny; Williamson, Carolyn; et al.
Abstract : Introduction: New HIV prevention strategies are urgently required. The discovery of broadly neutralising antibodies (bNAbs) has provided the opportunity to evaluate passive immunisation as a potential prevention strategy and facilitate vaccine development. Since 2014, several bNAbs have been isolated from a clade C-infected South African donor, CAPRISA 256. One particular bNAb, CAP256-VRC26.25, was found to be extremely potent, with good coverage against clade C viruses, the dominant HIV clade in sub-Saharan Africa. Challenge studies in non-human primates demonstrated that this antibody was fully protective even at extremely low doses. This bNAb was subsequently structurally engineered and the clinical variant is now referred to as CAP256V2LS. Methods and analysis: CAPRISA 012B is the second of three trials in the CAPRISA 012 bNAb trial programme. It is a first-in-human, phase I study to assess the safety and pharmacokinetics of CAP256V2LS. The study is divided into four groups. Group 1 is a dose escalation of CAP256V2LS administered intravenously to HIV-negative and HIV-positive women. Group 2 is a dose escalation of CAP256V2LS administered subcutaneously (SC), with and without the dispersing agent recombinant human hyaluronidase (rHuPH20) as single or repeat doses in HIV-negative women. Groups 3 and 4 are randomised placebo controlled to assess two (CAP256V2LS+VRC07-523LS; CAP256V2LS+PGT121) and three (CAP256V2LS+VRC07-523LS+PGT121) bNAb combinations administered SC to HIV-negative women. Safety will be assessed by the frequency of reactogenicity and adverse events related to the study product. Pharmacokinetic disposition of CAP256V2LS alone and in combination with VRC07-523LS and PGT121 will be assessed via dose subgroups and route of administration. Ethics and dissemination: The University of KwaZulu-Natal Biomedical Research Ethics Committee (BREC) and the South African Health Products Regulatory Authority (SAHPRA) have granted regulatory approval (trial reference numbers: BREC00000857/2019 and SAHPRA 20200123). Trial results will be disseminated through conference presentations, peer-reviewed publications and the clinical trial registry. Trial registration number: PACTR202003767867253; Pre-results.